Governance Quality of Political Stability and Rule of Law on Tax Compliance: A Mediation Analysis of Tax Morale - Mohd Allif Anwar Abu Bakar; Mohd Rizal Palil; Ruhanita Maelah (UKM Press, 2023)
The unresolved tax compliance dilemma gives a signal of consideration/ requirement of additional factors that will influence tax compliance, such as a governance-based approach. This paper investigates the association between governance quality and tax compliance, with tax morale as a mediator. Two dimensions of governance quality were considered: political stability and the rule of law. A quantitative survey of 592 salaried and selfemployed taxpayers in East Malaysia was conducted. Partial Least Squares-Structural Equation Modelling (PLSSEM) was used to analyse the data. Theoretically, the present research contributed to knowledge by supporting the significant role of tax morale in the mediation association between the rule of law and tax compliance. Tax compliance can also be improved when taxpayers have high tax morale. Practically, the findings aid policymakers and governments that an ideal governance mechanism via a stable political environment is crucial to increasing tax compliance. Nevertheless, the government’s approach to enforcing an effective rule of law was viewed as a more promising strategy for boosting the morale of taxpayers.